The McKenna rule and UK World War I finance - James M. Nason; Shaun P. Vahey (Federal Reserve Bank of Atlanta, 2007)
The United Kingdom employed the McKenna rule to conduct fiscal policy during World War I (WWI) and the interwar period. Named for Reginald McKenna, Chancellor of the Exchequer (1915–16), the McKenna rule committed the United Kingdom to a path of debt retirement, which we show was forward-looking and smoothed in response to shocks to the real economy and tax rates. The McKenna rule was in the tradition of the English method of war finance because the United Kingdom taxed capital to finance WWI. Higher rates of capital taxation also paid for debt retirement during and subsequent to WWI. The United Kingdom was motivated to implement the McKenna rule because of a desire to achieve a balance between fairness and equity. However, the McKenna rule adversely affected the real economy, according to a permanent income model. WWI and interwar U.K. data support the prediction that real activity is lower in response to higher past debt retirement rates.
Keywords: E6; N4; 330; war finance; McKenna rule; debt retirement; capital income tax rate; permanent income; Finanzpolitik; Kriegsfinanzierung; Haushaltskonsolidierung; Steuerpolitik; Wirkungsanalyse; Großbritannien